Dynamics of Manufacturing Competitiveness in South Asia: Analysis through Export Data - Hans-Peter Brunner; Massimiliano Calì (Asian Development Bank (ADB), 2005)
The outstanding export performance of South Asian countries (India in particular) over the 1990s has prompted some observers to see in it the roots of an export-led growth similar to that of its Southeast Asian neighbors. We employ export unit values (UVs) cum real competitiveness analysis to the manufacturing sector of four South Asian countries (with particular focus on India), in order to investigate the determinants of this apparent success. Shifts toward higher UVs relative to technology leaders serve as the most appropriate indication of underlying structural changes, and such change is manifested in technology closing-up processes among countries. According to our indices, the export competitiveness of South Asian countries (except Pakistan) seems to have slightly improved relative to its Southeast Asian comparators, but not relative to the Organisation for Economic Co-operation and Development. South Asian export growth has been mainly driven by relative quantity expansion through a reduction in relative costs rather than relative quality improvement. Such expansion has been concentrated in naturalresource-intensive, standard technology-intensive (in India), and labor-intensive sectors (in Bangladesh). On the other hand, the more technology-intensive sectors in India still suffer from a significant gap relative to Thailand that has not been closing up in the last decade. These findings suggest some notes of caution in interpreting the recent good export performance of South Asian economies.
hdl:11540/1905
Keywords: 330; Internationale Wirtschaft; Export; Internationaler Wettbewerb; Industrie; Indien; Südasien